The Vocabulary Building Audio-Visual Media: An Innovation in Vocabulary Expertise - Syahroni Syahrul Pratama; Muhamad Sofian Hadi (Universitas Cokroaminoto Palopo, 2023)
The success of student learning cannot be separated from the appropriate media and learning strategies. With the support of appropriate resources and new technologies, adult learners may effectively learn languages on their own, anywhere. Lack of knowledge about new technologies lead students to the lack of vocabulary. The existence of new technology must also be supported by the ability of students to master the technology. In connecting with the abilities that students have, the teacher finds obstacles, especially for students with special needs, mentally disabled students. Audio-visual media in the form of Flash card, drawing book and animated learning videos are used in English subjects at SLB Ulaka Penca. This study was conducted to investigate whether or not Audio-visual could be effective media to enhance students’ vocabulary mastery. The findings in this study are in the form of Vocabulary Skills Innovation with the aim of knowing how effective the use of visual auditory strategies, known as the use of audio